2017
DOI: 10.1111/ijfs.13343
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of myosin regulatory light chain modulates actin–myosin interaction adverse to meat tenderness

Abstract: The objective of this study was to investigate the relationship between the dephosphorylation of myosin regulatory light chain and actin-myosin interaction after muscle homogenate was treated with alkaline phosphatase and phosphatase inhibitor. The myosin regulatory light chain was significantly dephosphorylated by alkaline phosphatase after incubation. Among different groups, dephosphorylated myosin regulatory light chain to a much greater extent leads to a lower actomyosin dissociation degree, thereby raisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In skeletal muscle, the most abundant myofibrillar proteins are actin and myosin, which forms thick and thin filaments. A key step in ageing meat is the weakening of the actomyosin interaction, which causes changes in meat texture (Gao et al, 2017). In addition, tropomyosin and troponin, which form complexes with F-actin filaments, are also involved in muscle contraction; hence, these structural proteins are closely associated with tenderness.…”
Section: Resultsmentioning
confidence: 99%
“…In skeletal muscle, the most abundant myofibrillar proteins are actin and myosin, which forms thick and thin filaments. A key step in ageing meat is the weakening of the actomyosin interaction, which causes changes in meat texture (Gao et al, 2017). In addition, tropomyosin and troponin, which form complexes with F-actin filaments, are also involved in muscle contraction; hence, these structural proteins are closely associated with tenderness.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, multiple posttranslational modifications in postmortem muscle, such as phosphorylation, ubiquitylation, acetylation, methylation and alkylation, are considered. Protein phosphorylation has been especially extensively studied with regard to meat quality …”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation alters the proteolytic susceptibility of myofibrillar proteins and prevents myofibrillar protein degradation by μ‐calpain . Gao et al . suggested that dephosphorylation of myosin regulatory light chain alters the actomyosin dissociation and thus meat tenderness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversible protein phosphorylation catalysed by protein phosphatases and protein kinases alters protein structure and function, including protein-protein interactions and protein biological activity (Murray & Steck, 1984;Chu & Silverstein, 2012). Previous studies have revealed that phosphorylation of myofibrillar proteins may affect actomyosin dissociation through muscle contraction (Chen et al, 2016), especially the phosphorylation of myosin regulatory light chain (MRLC) (Gao et al, 2017). Phosphorylation of MRLC was first discovered in rabbit skeletal muscle and then in the myocardium (Perrie & Perry, 1970;Perrie et al, 1973;Frearson & Perry, 1975).…”
Section: Introductionmentioning
confidence: 99%